The Truth and False in the Magnetic Treatment of Water and Fuels - González Arias, A. (Revista Cubana de Física; Vol 25 No 2B (2008), 2008)
Magnetic water treatment causes a decrease of calcium carbonate crusts in pipes and boilers. Main parameters to take into account are the intensity and distribution of magnetic elements, water velocity and pipe material. However, sometimes the procedure has been labeled as 'pseudoscience', maybe because together with the proved reports, fictitious ones often also appear. A review on recent papers show the validity of the procedure when applied to suppress crusts. Some reports about other non-demonstrated magnetic treatments are mentioned.